The Prognostic Impact of Protein Expression of E-Cadherin-Catenin Complexes Differs between Rectal and Colon Carcinoma - Rolf Aamodt; Johan Bondi; Solveig Norheim Andersen; Arne Bakka; Geir Bukholm; Ida R. K. Bukholm (Gastroenterology Research and Practice)
The E-cadherin-catenin complex provides cell-cell adhesion. In order for a carcinoma to metastasize, cancer cells must let go of their hold of neighboring cells in the primary tumor. The presence of components of the E-cadherin-catenin complex in 246 rectal adenocarcinomas was examined by immunohistochemistry and compared to their presence in 219 colon carcinomas. The expression data were correlated to clinical information from the patients' records. There were statistically significant differences in protein expression between the rectal and the colon carcinomas regarding membranous 𝛽-catenin, 𝛾-catenin, p120-catenin, and E-cadherin, as well as nuclear 𝛽-catenin. In the rectal carcinomas, there was a significant inverse association between the expression of p120-catenin in cell membranes of the primary tumors and the occurrence of local recurrence, while membranous protein expression of 𝛽-catenin was inversely related to distant metastases.